FORMATION OF ECOLOGICAL NETWORKS BASED ON LANDSCAPE CONNEC-TIVITY MODELING (Scientific journal of the Fergana State University, 2026)
This article provides a scientific analysis of landscape ecological connectivity modelling, including the structural and functional characteristics of connectivity and its significance for ecosystem stability—key concepts in modern landscape ecology. The study discusses anthropogenic changes in geosystems, fragmentation processes, and their impacts on biodiversity. It also examines how landscape configuration, as well as the shape, size, and spatial arrangement of natural areas, influence species migration, genetic exchange, and ecosystem resilience. The article offers a comparative analysis of approaches and criteria used to assess structural and functional landscape connectivity. This approach holds important practical value for nature conservation, ecological corridor planning, biodiversity preservation, and the improvement of regional environmental policy.